1986
DOI: 10.1038/clpt.1986.101
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of midodrine, an antihypotensive agent

Abstract: Midodrine is an orally active adrenergic agonist useful in the treatment of hypotension. We have investigated the pharmacodynamics of its active metabolite after oral midodrine therapy in nine patients with severe orthostatic hypotension. Peak plasma levels of the metabolite were reached in 60 to 90 minutes and ranged from 25 to 56 ng/ml. The mean values for distribution volume, plasma clearance, and t1/2 were 4.0 L/kg, 23 ml/min/kg, and 2.1 hours, respectively. Heart rate increased after 5 to 10 mg doses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…Blood-brain barrier permeability and CNS effects are unknown at excessively high blood concentrations, multiple times that of the original study by Zachariah et al [5]. The same study also lists drowsiness as an adverse effect.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Blood-brain barrier permeability and CNS effects are unknown at excessively high blood concentrations, multiple times that of the original study by Zachariah et al [5]. The same study also lists drowsiness as an adverse effect.…”
Section: Discussionmentioning
confidence: 96%
“…Its mechanism of action is to increase peripheral venous resistance and decrease venous capacity, hence increasing the supine and standing blood pressure [4,7]. Notable side effects include compensatory reflex bradycardia [5], urinary urgency or retention, pilomotor reactions [2], pruritus and supine hypertension [1] and risk of bradycardia due to an alpha mediated vagal reflex [3]. Previous studies at therapeutic doses (10 mg) showed minimal or no central nervous system (CNS) side effects as it has poor absorption across the blood-brain barrier [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This me tabolite induces vasoconstriction of both arterioles and venous capacitance vessels and thus preventing peripher al venous pooling [9,10], This drug does not possess direct central nervous or cardiac effects and is well absorbed after oral administration. It has been used for many years for the treatment of orthostatic hypotension due to autonomic failure such as Shy-Drager syndrome as well as Bradbury-Eggleston syndrome and has been proved to be effective [11][12][13], Recently, several previous studies [14,15] have shown the efficacy of midodrine in patients with hemodialysis-related hypotension.…”
Section: Introductionmentioning
confidence: 99%
“…M idodrine ( 1 -[2',5'-dimethoxyphenyl-1 ]-2-glycinamido-ethanol( 1 )-hydrochloride) is the prodrug of a specific ai-adrenergic agonist, desglymidodrine [8,9]. This me tabolite induces vasoconstriction of both arterioles and venous capacitance vessels and thus preventing peripher al venous pooling [9,10], This drug does not possess direct central nervous or cardiac effects and is well absorbed after oral administration.…”
Section: Introductionmentioning
confidence: 99%